DETERMINATION OF THE BENEFITS AND RISKS OF PEER-TO-PEER (P2P) LENDING: A SOCIAL NETWORK TEORY APPROACH - Purkayastha, Nadia Nahar; Tuzlukaya, Şule Erdem (Copernican Journal of Finance & Accounting, 2021)
Peer-to-Peer lending which is also known as P2P is an online financial investment platform where individual investors finance projects by lending money to individual borrowers through social networks. P2P models usually contributing to less privileged people especially entrepreneurs and frontier groups who do not have access to formal financial services. However, due to the economic conditions and lack of government support, P2P lending platforms in developing countries often fail to reveal the ‘credit history’ and ‘indebtedness’ of individual borrowers which have an expressive impact on loan performance. The objective of this study is to demonstrate theoretically the factors those influence the lenders to participate in the P2P lending platform in developing countries and the associated risks. For this purpose, two propositions are developed to examine the factors to demonstrate the role of the social network is also combined to further explain the P2P lending.